2011
DOI: 10.1534/genetics.111.127217
|View full text |Cite
|
Sign up to set email alerts
|

Prion-Forming Ability of Ure2 of Yeasts Is Not Evolutionarily Conserved

Abstract: ABSTRACT[URE3] is a prion (infectious protein) of the Saccharomyces cerevisiae Ure2p, a regulator of nitrogen catabolism. We show that wild S. paradoxus can be infected with a [URE3] prion, supporting the use of S. cerevisiae as a prion test bed. We find that the Ure2p of Candida albicans and C. glabrata also regulate nitrogen catabolism. Conservation of amino acid sequence within the prion domain of Ure2p has been proposed as evidence that the [URE3] prion helps its host. We show that the C. albicans Ure2p, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 78 publications
6
46
1
Order By: Relevance
“…Hsp104p dramatically promotes the prion conversion of Ure2p from C. albicans: We used the cerevisiae strain BY302 having the C. albicans URE2 open reading frame in place of that of cerevisiae, but driven by the cerevisiae URE2 promoter (Edskes et al 2011). Among the genes derepressed on inactivation of Ure2p by prion formation is DAL5, encoding the allantoate permease (Turoscy and Cooper 1987).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsp104p dramatically promotes the prion conversion of Ure2p from C. albicans: We used the cerevisiae strain BY302 having the C. albicans URE2 open reading frame in place of that of cerevisiae, but driven by the cerevisiae URE2 promoter (Edskes et al 2011). Among the genes derepressed on inactivation of Ure2p by prion formation is DAL5, encoding the allantoate permease (Turoscy and Cooper 1987).…”
Section: Resultsmentioning
confidence: 99%
“…BY302 also carries ADE2 under control of the DAL5 promoter so that an active Ure2 alb gives red Ade 2 colonies and an inactive Ure2 alb results in white Ade 1 clones (Brachmann et al 2005). The C. albicans Ure2 protein (Ure2p alb ) can form the [URE3alb] prion in S. cerevisiae (Edskes et al 2011) and, as with other prions (Wickner 1994), the frequency of prion formation is dramatically increased when this protein is overexpressed (Edskes et al 2011 Figure S1). …”
Section: Resultsmentioning
confidence: 99%
“…Extensive barriers to transmission of [PSI+] between wild S. cerevisiae have been found, suggesting that this protection from "catching" a prion has been selected in evolution (34). The notion that prion-forming ability is generally conserved (46) is not true for Ure2p, as the Saccharomyces castellii, Kluyveromyces lactis, and Candida glabrata Ure2ps cannot become [URE3] even though they are closely related to that of S. cerevisiae Ure2p, whereas the more distantly related Candida albicans Ure2p can form a prion (33,49,50). Prion-forming ability appears to be sporadic rather than conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while many (but not all) close or distant Sup35p and Ure2p orthologs have been shown to have prion forming abilities when expressed in Saccharomyces cerevisiae, evidence for such prion propagation in their natural hosts is rather scarce. [66][67][68][69][70][71][72][73] This may be due to unique properties (e.g., molecular chaperones, quality-control sub-cellular compartments, etc.,) evolved by S. cerevisiae laboratory strains that are required for the maintenance and propagation of prions. In a recent study, we showed for the first time that a single amino-acid change within the C-terminal domain of Sup35p dramatically affects its prion properties.…”
Section: The [Psi + ] and [Ure3] Prionsmentioning
confidence: 99%